The fourth ruby - Hannibal, James R. (Section 13, 2017)
Jack Buckles, a thirteenth-generation tracker whose senses are on the fritz, and Gwen Kincaid, a clerk hoping to become an apprentice quartermaster, are framed for stealing a legendary jewel--one of a set of rubies thought to bring the owner loyalty, knowledge, and power--and they must locate the remaining rubies before the thief does or risk his unleashing a reign of terror worse than Genghis Khan's.